Genetic effects of Red Lettuce Leaf genes on red coloration in leaf lettuce under artificial lighting conditions. Issue 4 (2nd September 2022) - Wada, Kaede C.; Inagaki, Noritoshi; Sakai, Hiroaki; Yamashita, Hiroto; Nakai, Yusuke; Fujimoto, Zui; Yonemaru, Jun‐ichi; Itoh, Hironori
Abstract: Some cultivars of lettuce accumulate anthocyanins, which act as functional food ingredients. Leaf lettuce has been known to be erratic in exhibiting red color when grown under artificial light, and there is a need for cultivars that more stably exhibit red color in artificial light cultivation. In this study, we aimed to dissect the genetic architecture for red coloring in various leaf lettuce cultivars grown under artificial light. We investigated the genotype of Red Lettuce Leaf ( RLL ) genes in 133 leaf lettuce strains, some of which were obtained from publicly available resequencing data. By studying the allelic combination of RLL genes, we further analyzed the contribution of these genes to producing red coloring in leaf lettuce. From the quantification of phenolic compounds and corresponding transcriptome data, we revealed that gene expression level‐dependent regulation of RLL1 (bHLH) and RLL2 (MYB) is the underlying mechanism conferring high anthocyanin accumulation in red leaf lettuce under artificial light cultivation. Our data suggest that different combinations of RLL genotypes cause quantitative differences in anthocyanin accumulation among cultivars, and some genotype combinations are more effective at producing red coloration even under artificial lighting. Abstract : In lettuce grown under artificial light, four RLL genes and ANS play important roles in leaf coloration. Different combinations of their genotypes produce quantitative differences in anthocyanin accumulation among cultivars.